Habitual Tea Consumption Reduces Prostate Cancer Risk in Vietnamese Men: a Case-Control Study - Hoang, V.; Lee, Andy; Pham, N.; Xu, Dan; Binns, Colin (Asian Pacific Organization for Cancer Prevention, 2016)
Background: An upward trend has been noted for the incidence of prostate cancer (PCa) in Vietnam, but information is limited on modifiable factors associated with this form of cancer. This case-control study was conducted to ascertain any relationship between habitual tea consumption and PCa risk. Materials and Methods: Two hundred and fifty-three incident patients with histologically confirmed PCa and 419 (340 community-based and 79 hospital-based) controls, matched by age, were recruited in Ho Chi Minh City during 2013-2015. Information on frequency, quantity and duration of tea consumption, together with demographics, habitual diet and lifestyle characteristics, was obtained by direct interviews using a validated questionnaire. Logistic regression analyses were performed to assess associations between tea consumption variables and PCa risk. Results: The control subjects reported higher tea consumption levels in terms of cumulative exposure, frequency and quantity of tea drank than the PCa patients. After accounting for confounding factors, increasing tea consumption was found to be associated with reduced risk of PCa. The adjusted odds ratios (95% confidence intervals) were 0.52 (95% CI 0.35-0.79) and 0.30 (95% CI 0.18-0.48) for participants drinking 100-500 ml/day and > 500 ml/day, respectively, relative to those drinking < 100 ml/day. Significant inverse dose-response relationships were also observed for years of drinking and number of cups consumed daily (P <0.01). Conclusion: Habitual tea consumption is associated with a reduced risk of PCa in Vietnamese men.